Analysis of Ear, Nose and Throat Manifestations in COVID-19 Patients - El-Anwar,Mohammad Waheed (2021)
Abstract Introduction Coronavirus disease 2019 (COVID-19) has dramatically spread all over the world, crossing the borders of all countries. It is presented mainly by lower respiratory tract symptoms such as fever, cough, dyspnea, and chest tightness. However, COVID-19 causes different upper respiratory tract-related symptoms including nasal congestion, sore throat, and olfactory dysfunction. Objective To discuss different ear, nose and throat (ENT) manifestations in COVID-19-positive patients and their relation to other manifestations and to the severity of COVID-19. Methods We detected ENT manifestations in polymerase chain reaction (PCR)-confirmed positive COVID-19 patients at Zagazig Isolation Hospitals (Zagazig University hospitals, Zagazig Chest hospital, Al-Ahrar hospital, and Zagazig Fever hospital) with proportional allocation in the period from April 15 to June 15, 2020. All patients were subjected to full history taking and COVID-19 was categorized into 4 classes of severity after all patients underwent computed tomography (CT) of the chest. Afterwards, the collected data was analyzed and compared. Results Among the included 120 COVID-19 patients, the most frequent reported ENT manifestations were; sore throat (30%), nasal congestion (28.3%), nasal obstruction (26.7%), sneezing (26.6%), headache (25%), smell and taste dysfunction (25%), rhinorrhea (20%), upper respiratory tract infection (URTI) (15%), and tonsil enlargement (10%). The most common non-ENT manifestations were fever (88.3%), cough (63.3%), and dyspnea (45%). Conclusion Fever and cough are the dominant symptoms of COVID-19, but ENT manifestations for COVID-19 are common and should be a part of the suspected clinical criteria for COVID-19, particularly if the nasal examination was nonsignificant. The most common symptoms are sore throat, followed by nasal congestion and obstruction, headache, and lastly, olfactory dysfunction.